Analysis and Modelling to Mapping Riparian Vegetation in the Usumacinta Watershed, Mexico - Daniel, M. Lopez L; Aristides, Saavedra G (European Journal of Applied Sciences, 2023)
Riparian vegetation of fluvial systems is a complex of vegetation units along the river network or water bodies. Despite covering a relatively small area, riparian vegetation provides many ecosystem services; however, these ecosystems experience multiple pressures because of land use change, timber harvesting, mining, deforestation. Managing for healthy native riparian vegetation and connected floodplains is a central part of river management, to to carry it out this effort, a first step is to know the spatial distribution and the present state of such ecosystem. It is the objective of this study to illustrate how different elements of the geo-spatial information sciences, particularly remote sensing and spatial analysis and modeling, can contribute significantly in mapping the potencial an present state of riparian ecosystem. In this study, to mapping riparian vegetation two approximations were conducted, the first one namely the valley bottom approximation, which was applied to the total area of Usumacinta watershed, and the other one the geomophological mapping, which was applied in the low land area. The results shows that most area of riparian vegetation has been destroyed, by introduction of grasslands and crops; only approximately 26 % of the area are in good conditions. An important conclusion is that mapping this especial and important ecosystems is a firsts step to carry out a reclamation program, and establish a political measures to its conservation.